2017
DOI: 10.21577/0103-5053.20170072
|View full text |Cite
|
Sign up to set email alerts
|

Rice Husk Ash as Raw Material for the Synthesis of Silicon and Potassium Slow‑Release Fertilizer

Abstract: Rice husk ash (RHA) is a waste material produced in large quantities in many regions worldwide, and its disposal can be problematic. This work describes a method for using RHA to synthesize silicon and potassium slow-release fertilizer. The extraction of silica from RHA was accomplished by alkaline leaching with KOH. Different KOH concentrations and reaction times were evaluated and the best production of K 2 SiO 3 solution was achieved using 6 mol L -1 and 6 h, respectively. The fertilizer was synthesized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…França et al investigated silica extraction from rice husk ash using KOH solution with various concentration and showed that 32.3% recovery from ash was achieved using 1.0 M solution for 6 hr. [45]. The difference between biological treatment and thermal treatment was not too far or less than 50%, it means that biological process could be an alternative to the thermal one in a series of extraction procedures.…”
Section: Ilhamy Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…França et al investigated silica extraction from rice husk ash using KOH solution with various concentration and showed that 32.3% recovery from ash was achieved using 1.0 M solution for 6 hr. [45]. The difference between biological treatment and thermal treatment was not too far or less than 50%, it means that biological process could be an alternative to the thermal one in a series of extraction procedures.…”
Section: Ilhamy Et Almentioning
confidence: 99%
“…3Bio Journal of Biological Science, Technology and Management 2(2): [39][40][41][42][43][44][45][46] Nyuanti et al Management recommendation to manage invasive species for A. riparia is aimed to reduce the environmental, economic, and social impacts of invasive species. This particular management approach is recommended by [10] especially for invasive species with high risk categories.…”
Section: Invasive Species Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Therefore, these reports evidence the need to prospect fertilizer technologies which release K in a controlled process according to plant demands aiming to improve fertilizer efficiency, including the reduction of both on K loss and the need of split application. 4,5 In fact, several studies have been performed into using different materials as slow-release K-fertilizer, such as rice husk ash for the synthesis of silicon and potassium, 6 K-feldspar (KAlSi 3 O 8 ) 7 and chrysotile/K 2 HPO 4 . 8 Serpentinite, a metamorphic rock with general approximate formula [Mg 3 Si 2 O 5 (OH) 4 ], is found in different places on the surface of the world with global reserves estimated in hundreds of millions kg.…”
Section: Introductionmentioning
confidence: 99%
“…9 Therefore, due to its abundance, nontoxicity, low cost and biodegradability, biomass has been widely used as SRF material. França et al 10 used rice husk ash as the raw material to prepare a slow-release fertilizer containing silicon and potassium. Wen et al 11 reported the synthesis of a corncob-based semi-interpenetrating polymer network slow-release nitrogen fertilizer.…”
Section: Introductionmentioning
confidence: 99%